PHYTOPLANKTON OF AYAKAGIMTA LAKE - Shamsiev Naim Amonovich; Aripov Baxrtiyor Farmanovich; Usmonova Dilnoza Baratovna; Amonova Dilfuza Naimovna (International Engineering Journal For Research & Development, 2020)
This article presents the composition of phytoplankton species of the Ayakagimta lake, the development, quantity and biomass variation of phytoplankton in the lake, phytoplankton of the Ayakagimta lake has been widely used as a nutrient and provides information on the increase in fish productivity.